Using modified tutorless problem-based learning approach with ‘SET triggers’ to teach diabetes mellitus to undergraduate medical students - Patil, Karan Shrikant; Gupta, Dinesh Chandra; Ganeshpure, Swapnil (International Journal of Advances in Medicine, 2019)
Background: The purpose of this study was to introduce modified form of conventional problem-based learning (PBL) i.e. “Tutor less PBL” in educating medical students about type 2 diabetes mellitus (T2DM). Medical students are future physicians and can be effective healthcare professionals to screen and manage diabetes at community level. Poor levels of awareness as well as lacunae in teaching diabetes have been reported among medical students. The study aimed to assess the knowledge of undergraduate medical students about T2DM by using “Tutorless PBL” method. Methods: Sixty-two 8th semester medical students from one of the private medical colleges in Mumbai city attained knowledge about T2DM through “Tutorless PBL” and “conventional PBL”. “A structured set of engagements triggers” (SET) was used in Tutorless PBL. Students responded through pre and post-test questionnaires and ‘student’s unpaired t test’ compared their test scores. Fourteen item questionnaires with Likert scale evaluated students’ feedback about both methods. Results: The post test scores were more for students in “Tutor less group” than in “tutored group” (15.37 vs. 14.01). The difference was statistically significant (t=5.87, p<0.001). All (100%) students appreciated both methods for enhancing their knowledge about T2DM. “Tutor less PBL” was found to be more effective than “conventional PBL” in promoting self-learning and critical thinking abilities. Conclusions: Both methods were beneficial to students in terms of clarifying the topic, improving group interaction and yielding self-directed learning. Tutorless problem-based learning can be an effective option especially in resource (faculty) limited setting.